Mechanical improvement in acetal composites reinforced with graphene nanotubes and Teflon fibers using loss functions - Makkuva Chaitanya Mayee; Vommi Vijaya Babu (Journal of the Mechanical Behavior of Materials)
This study focuses on improving the mechanical strength, wear resistance, and frictional properties of acetal, a popular engineering polymer, by incorporating graphene nanotubes (GNTs) and Teflon fibers. Despite acetal’s low friction and chemical resistance, its mechanical limitations often restrict its use in high-load, wear-intensive applications. To overcome this, researchers developed composite materials using a melt-blending technique with varying concentrations of GNTs (0.25–2.0 wt%) and Teflon fibers (5–20 wt%). Key findings include a significant enhancement in acetal’s mechanical properties with the addition of 1 wt% silane-treated GNTs, resulting in increases of 34% in tensile strength, 48% in tensile modulus, 44% in flexural strength, and 47% in flexural modulus compared to pure acetal. Furthermore, incorporating 10 wt% Teflon fibers reduced wear rates by 58% and improved frictional performance. The optimized composite, containing 1 wt% GNTs and 10 wt% Teflon fibers, demonstrated superior mechanical and tribological properties, making it suitable for demanding engineering applications such as gears. This research underscores the potential of acetal composites for enhancing performance and durability in mechanical components, paving the way for more efficient and sustainable engineering solutions while advancing polymer composite material development.